(3QSGFd GdMQjQjs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO ajgG(B: (3hVGYa EbHGdg hGfGdg ai GdOGQjf BeGdg hef cdGeg GdTaGYg Edi fbjH GdfbHGA ai Mb GdTQja CHj Ydi s
(3BNQgG (B:s
(3CHjGJ cJHgG dCHi GdaJM SdGQ Hf RjO jSJgOjg eOGOkG aGdYLjH GdYLGH Cfc JSOi YfO JShjOgG jOnG HjVGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJ hGdJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs